Prayer on the Prophet between Devotion and Scholarship - Petrone, Michele (Oriente moderno, 2022)
Prayer on the Prophet constitutes a common practice for all Muslims, often based on collections of taṣliyas that started appearing from the 14th century. This study aims at tracing the early developments of this literature, from jurisprudential works on the liceity and merits of the practice, to the naissance of new and articulated forms of prayer. This will also help detecting the role played by the institutionalization of Sufism in shaping the approach to the figure of the Prophet outside Sufi circles.